Improving venous thromboembolism prophylaxis through critical thinking and health informatics. Issue 2 (2nd June 2020) - Taha, Haytham; Govindraj, Ezhil; Jaber, Filestin; Shehadeh, Ghadah; Kelly, Bernadette; Krishnan, Siny; Hamed, Wala Kamal
Abstract : Venous thromboembolism (VTE) is a leading cause of preventable morbidity and mortality in hospitalised patients. Mafraq Hospital, a 450-bed tertiary-level hospital in Abu Dhabi, United Arab Emirates, has identified VTE prevention as a critical patient safety measure and VTE prophylaxis as a key performance indicator (KPI). Mafraq Hospital VTE prevention policy states that all admitted adult patients 18 years and above should receive a VTE risk assessment, and all patients identified at risk of VTE with no contraindications should receive appropriate VTE prophylaxis within 24 hours of admission. In a move towards safer practices, our governing body, Abu Dhabi Health Services SEHA, has raised the VTE prophylaxis KPI target from 85% to 95% for all admitted adult patients within 24 hours of admission. Our average VTE prophylaxis rate was 87%, and achieving this new target was a challenge. We conducted this study on Mafraq Hospital Medical and Surgical wards. The study period was 12 months, from July 2018 to June 2019, and a total of 5475 patients were evaluated. Our aim was to improve VTE prophylaxis rates in order to ensure patient safety and reduce preventable harm. We used Caprini Model electronic VTE risk assessment computerised decision support tool to help identify VTE risk. A multidisciplinary task force team was formed and led this quality improvement project. The purpose of this publication was to indicate the quality improvement interventions implemented to enhance compliance with VTE prophylaxis using integrated critical thinking and health informatics and the outcomes of those interventions. Through implementing critical thinking and health informatics interventions, our VTE prophylaxis within 24 hours of admission rates improved from an average 87% in July 2018 to above 98%, and this improvement was sustained over the last 3 months of the study period April through June 2019.